EVALUASI PERESEPAN PADA PASIEN GERIATRI DI KLINIK PENYAKIT DALAM INSTALASI RAWAT JALAN RSUD K.R.M.T WONGSONEGORO SEMARANG - Mulyani, Tri; Rukminingsih, Fef (Jurnal Riset Kefarmasian Indonesia, 2020)
The medical problems encountered in geriatric patients cause the prescribing to be susceptible to polypharmacy so that the possibility of creating Drug Related Problems (DRPs) is likely. Beers Criteria is one method to avoid the occurrence of DRPs. This study aims to evaluate prescribing of geriatric patients based on the Beers Criteria 2015 at the internal medicine clinic in the outpatient installation of K.R.M.T Wongsonegoro Hospital Semarang. This research was an descriptive observational study using retrospective data from geriatric patients' medical records at the internal medicine clinic in the outpatient installation of K.R.M.T Wongsonegoro Hospital Semarang in the period October - December 2017. A total of 300 medical records were taken at simple random as samples. Data for each patient were only taken once during the study period. The patient is a national health insurance participant and is ≥60 years old. The data obtained was then identified using Beers Criteria 2015. Based on the prescription of 300 geriatric patients in the internal medicine clinic in Wongsonegoro Hospital Semarang, it is known that 88,33% patients received prescription included in Beers Criteria 2015. The five medicine most prescribed are Na diclofenac, omeprazole, digoxin, ranitidine, and diazepam. Medications included in Beers Criteria are medicine that should not be given to geriatric patients so that caution is needed in the use of these medicine.